Measuring and tracking adaptation outcomes: learnings and opportunities - Nowak, Andreea C.; Segnon, Alcade; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Presentation for the AICCRA Independent Science Committee Meeting (May 2023). Objectives: Summarize learnings from measuring progress and effectiveness of adaptation to climate change; Share and discuss ideas on a research and action agenda for advancing adaptation tracking